2001
DOI: 10.1034/j.1399-6576.2001.450105.x
|View full text |Cite
|
Sign up to set email alerts
|

A single‐injection, multi‐segmental paravertebral block – extension of somatosensory and sympathetic block in volunteers (Note)

Abstract: One-sided extended analgesia (sensory loss) follows the paravertebral injection of lidocaine. A large ipsilateral sympathetic block is observed without change in pulse rate and with no hypotension. These are all characteristics of an optimal regional block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 11 publications
3
39
0
Order By: Relevance
“…Kairaluoma [2] et al (2006) in his study demonstrated the longterm beneficial effects of Paravertebral Block (PVB) on postoperative pain. Similar results were demonstrated by Saito [3] et al (2001) and Terheggen M et al [4] (2002).…”
supporting
confidence: 80%
“…Kairaluoma [2] et al (2006) in his study demonstrated the longterm beneficial effects of Paravertebral Block (PVB) on postoperative pain. Similar results were demonstrated by Saito [3] et al (2001) and Terheggen M et al [4] (2002).…”
supporting
confidence: 80%
“…However, thoracic epidural anaesthesia is not the only regional anaesthetic technique for rib fractures. Thoracic paravertebral blocks are also effective in patients with rib fractures and are associated with less hypotension than thoracic epidural anaesthesia, likely due to their unilateral sympathetic blockade [6,14,16]. Because of this reduced degree of sympatholysis, thoracic paravertebral blocks may be preferable to thoracic epidural anaesthesia in patients at risk for heart block.…”
Section: Discussionmentioning
confidence: 95%
“…The pain signals of renal origin travel through afferent Aδ and C sympathetic fibers on the adventitia of the renal arteries, reaching the renal and intermesenteric plexus, then pass through the lowest splanchnic nerve, to enter the spinal cord via T11 -L2 dorsal roots and finally relay on the medial medullary reticular formation [23].…”
Section: Discussionmentioning
confidence: 99%